Longitudinal development of match performance in elite field hockey players training within a high-performance environment - Lam, E. P.; Sunderland, C. D.; Morris, J. G.; Furlong, L. M.; Forouhandeh, A.; Bevan, T.; Mason, B. S.; Tolfrey, K.; Barrett, L. A. (Journal of Sports Sciences, 2026)
This study examined whether the performance characteristics of male university field hockey players were associated with undergraduate degree year of study. Fifty-two male university field hockey players (age 20.8 ± 2.4 years, stature 1.79 ± 0.06 m, body mass 75.8 ± 8.3 kg) were monitored over 85 matches played across four national league seasons in the UK (2018-2022) using 15 Hz Global Positioning System units and heart rate monitors. Total distance, high-speed running distance (=15.5 km.h-1), accelerations (=2 m.s-1), decelerations (= -2 m.s-1), average heart rate and percentage of time spent at >85% of maximum heart rate were compared between 1st year, 2nd year and final year players across 1090 player-match files. Hierarchical linear modelling of performance characteristics (Match - level 1, Player - level 2), normalised to 70 min match time, found that the total and high-speed running distance covered by final year players was lower compared to 2nd year players (by 163 m and 127 m, respectively, both p < 0.05). With increased training experience in a high-performance programme, running performance required to perform optimally could be reduced in university players due to the high level of match performance achieved, development of game understanding and improved technical ability.